Bioactive Compounds from Natural Products: Separation, Characterization and Applications - Vamanu, Emanuel (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Dear colleagues, This Special Issue aims to publish new and innovative research that could demonstrate the therapeutic potential of natural health products, through relevant in vitro and/or in vivo biological activities, to prevent or alleviate degenerative diseases. The interaction of natural health products with human microbiota represents an essential aspect, because it could modulate the microbial pattern and alleviate more of a chronic disease's effects in the case of type 2 diabetes, cardiovascular dysfunctions, neurodegenerative diseases, and inflammatory colon pathologies. Additionally, you are invited to send research based on the effect of different extracts or functional foods used in degenerative pathologies and interactions with human microbiota. We aim to identify new data on in vitro/in vivo research that could demonstrate the bioavailability of natural compounds and the relationship with antioxidant/antimicrobial capacity. Modulated microbiota aspects are expected to be published based on the interaction with natural compounds, natural sweeteners, or other molecules that influence the colon health status.